Wind power prediction analysis by ANFIS, GA-ANFIS and PSO-ANFIS. Issue 3 (3rd April 2022) - Kumar, Neeraj; Sudha, K.; Tharani, Kusum
Abstract: The wind generation technology is improving step by step with the development of science and innovation. Certain characteristics of wind include instability, irregularity, low vitality and so forth. Wind control is unpredictable in nature. When extensive wind farms are incorporated into the power grid, there will be trouble in power equalization and power regulation because of vast fluctuation of wind. Meticulous wind control techniques can reduce the installation cost of the system and the impacts on the grid can be greatly reduced. To improve the transient wind control, it is necessary to precisely utilize the various neural network techniques. In this paper, the non-linearities arising in wind control are greatly reduced by using the Genetic Algorithm, ANN, ANFIS and PSO methods.